The effect of the nose form on linear and angular lip position in Class II patients - Siddiqui, Tania Arshad; Sukhia, Rashna Hoshang; Hasan, Ahmad; Arshad, Ruhamaa; Mir, Hassam Anjum; Mansoor, Saad (Journal of the Pakistan Medical Association, 2026)
Objective: To determine the effect of nose form on linear and angular lip position on pre-treatment cephalometric soft tissue analysis. Method: The retrospective, cross-sectional, analytical study was conducted at the orthodontic department of Foundation University College of Dentistry and Hospital in Islamabad, and comprised data from October to December 2023 of patients aged 18-25 years presenting with no prior history of orthodontic treatment and craniofacial anomalies and syndromes. Pre-treatment lateral cephalograms were manually traced by a single experienced investigator. The sample was divided into two horizontal groups, using point A-nasion-point B angle. Comparisons were made based on gender and sagittal groups, and the effect of nasal profiles was assessed. Data was analysed using SPSS 23. Results: Of the 131 patients, 96(73.2%) were females with mean age 22.70±3.97 years, and 35(26.7%) were males with mean age 20.97±3.21 years. There were 65(49.6%) subjects in sagittal Class I group, and 66(50.4%) in sagittal Class II group. A significant and inverse relationship was noted for columellar length with linear position of the upper and lower lips to E and S lines (p<0.05). Inclination of the nasal base had the most effect on the naso-labial angle (p<0.05). Conclusion: Skeletal Class II had a prominent nose which created a relatively retrusive appearance of the upper and lower lips. Key Words: Cephalometry, Diagnosis, Nose, Aesthetics, Rhinoplasty.